Effect Of Ca Addition On Piezoelectric And Dielectric Properties In b0.93la0.02sr0.05(Zr0.52ti0.48)O3 (Plszt) System - Rashid, Tuan Nur Izzah Tuan Ab (2018)
Lead zirconate titanate (PZT) is a piezoelectric material which is most widely used in ceramics. La3+ and Sr2+ co-doped PZT (PLSZT) shows the improvement in piezoelectric and dielectric properties which were piezoelectric coefficient (d33), electromechanical coupling factor (kp) and dielectric permittivity (ɛᵣ). However, the d33 and kp still indicated a lower value for electronic device applications. In order to improve d33 and kp, the doping process and poling behaviour were investigated. In this research, Pb0.93La0.02Sr0.05(Zr0.52Ti0.48)O3 (PLSZT) ceramic was synthesized by high energy planetary ball milling for 40 hours and sintered at 1200 °C for 3 hours. The poling parameters (temperature, electric field and time) were studied based on design of experiment (DOE) in order to investigate the effect of poling parameter towards the piezoelectric and dielectric properties for PLSZT. Besides, a new dopant (CaCO3) for PLSZT was studied followed by sintering parameters (1100 °C to 1300 °C for 2 to 4 hours) for further improving their piezoelectric and dielectric properties. The optimum poling parameter shows a good d33 and ɛᵣ which were 320 pC/N and 1660, respectively. Poling parameters were optimized at T = 140 °C, Ef = 4 kV/mm and t = 20 min. Ca2+ doped PLSZT (PCLSZT) show that enhancement of d33, kp and ɛᵣ occurred at lower Ca addition. Optimum piezoelectric and dielectric properties were obtained at 0.005 mol% CaCO3 (PCLSZT0.005) sintered at 1200 °C for 3 hours with d33 = 430 pC/N, kp = 0.5866, ɛᵣ = 2450 and tan δ = 0.0426. In conclusion the addition of Ca2+ successfully increased the piezoelectric and dielectric properties of PLSZT.